Biochemical and neurosurgical analyses of circulating neuroglobin and somatic mutations in IDH1 gene in patients with traumatic brain injury. Issue 1 (31st December 2022) - Hassan, Mohammed H.; Saleem, Tahia H.; Ashraf, Omyma; Elsadek, Bakheet E.M.; Hamdan, Ali R.; El-Sawy, Samer A.
ABSTRACT: Traumatic brain injury (TBI) is one of the most common acute neurological illnesses, but the impact of numerous biochemical and genetic indicators on its neurological sequelae has yet to be examined.This work aims to assess the initial circulating neuroglobin (NGB) levels using ELISA assays and the frequency of genetic variants of isocitrate dehydrogenase isoform 1 (IDH1) [c.395 G˃A(R132H)] by restriction fragment length polymorphism using polymerase chain reaction technique (RFLP-PCR) in patients with traumatic brain injury (TBI). The severity of TBI was assessed using the Glasgow coma scale (GSC) and revised trauma scale (RTS). The outcome was evaluated using the Extended Glasgow Outcome Scale and Disability Rating Scale.This research involved 30 patients with TBI comparable with 30 matched healthy controls.The overall results revealed male predominance among TBI. There were significantly higher serum NGB levels among cases compared to the controls, and among patients with severe TBI than those with mild to a moderate degree, p ˂ 0.05 for both. Serum NGB levels were significantly negatively correlated to both GCS (r = −0.498, p = 0.005) and RTS (r = −0.521, p = 0.003). The serum NGB is better in predicting TBI severity (AUC = 0.715) compared to the outcome (AUC = 0.582). The frequencies of both wild and mutant types of IDH1 c.395 G˃A (R132H) showed non-significant differences in TBI patients in terms of severity or outcome, p˃0.05 for both.Serum NGB can be considered a valuable noninvasive marker for predicting the severity and outcome of TBIpatients. There is a lack of association of IDH1 genetic variants with the outcome or severity of TBI in Egyptian patients.